The Normalization of Deviant Organizational Practices: Wage Arrears in Russia, 1991–98 - Earle, John S.; Spicer, Andrew; Peter, Klara Sabirianova (Academy of Management Journal, 2010)
We apply a normalization of deviance model to understand the prevalence of the illegal practice of wage arrears, the delayed payment of wages, in Russia during the 1990s. Viewing organizational deviance as potentially self-reinforcing, we hypothesize that the frequent adoption of a deviant practice within a community makes it more likely that firms in that community will engage in deviance and less likely that injured stakeholders will oppose it. Our empirical analysis of wage arrears in Russia, based on panel data from a large, nationally representative sample of agricultural and industrial enterprises, supports our hypotheses.